The concurrent use of antithrombotic therapies and the risk of bleeding in patients with atrial fibrillation - Azoulay, Laurent; Dell’Aniello, Sophie; Simon, Teresa; Renoux, Christel; Suissa, Samy (Thrombosis and Haemostasis, 2013)
Patients with atrial fibrillation (AF) often receive, in addition to warfarin, antithrombotic drugs to manage other comorbid conditions. To date, few population-based studies have quantified the bleeding risk associated with the concurrent use of these therapies. The United Kingdom General Practice Research Database was used to identify a cohort of 70,760 patients newly-diagnosed with AF between 1993 and 2008. A nested case-control analysis was conducted within that cohort, and conditional logistic regression was used to estimate adjusted rate ratios (RRs) of bleeding associated with current use of warfarin, aspirin, and clopidogrel in single therapy, as well as in dual and triple therapy, as compared with non-use of any therapy. A total of 10,850 patients experienced a bleeding event during follow-up. In single therapy, warfarin was associated with the highest increased risk (RR: 2.08, 95% confidence interval [CI]: 1.95–2.23), followed by clopidogrel (RR: 1.57, 95% CI: 1.37–1.81) and aspirin (RR: 1.25, 95% CI: 1.17–1.34). In dual therapy, combinations containing warfarin were associated with a higher increased risk (warfarin-aspirin: RR: 2.87, 95% CI: 2.58–3.19, and warfarin-clopidogrel: RR: 2.74, 95% CI: 2.14–3.51), than those not containing warfarin (aspirin-clopidogrel: RR: 1.68, 95% CI: 1.44–1.97). Triple therapy of warfarin-aspirin-clopidogrel was associated with the highest increased risk (RR: 3.75, 95% CI: 2.71–5.19). This large population-based study suggests that while all antithrombotic therapies are associated with an elevated risk of bleeding, the risks increase in an additive fashion with dual and triple therapy, particularly in combinations containing warfarin.
Keywords: Atrial fibrillation; antithrombotic therapies; bleeding; populationbased